Mapping of Minimal Motifs of B-Cell Epitopes on Human Zona Pellucida Glycoprotein-3. (17th November 2011) - Xu, Wan-Xiang; He, Ya-Ping; Wang, Jian; Tang, Hai-Ping; Shi, Hui-Juan; Sun, Xiao-Xi; Ji, Chao-Neng; Gu, Shao-Hua; Xie, Yi
Abstract : The human zona pellucida glycoprotein-3 (hZP3) by virtue of its critical role during fertilization has been proposed as a promising candidate antigen to develop a contraceptive vaccine. In this direction, it is imperative to map minimal motifs of the B cell epitopes (BCEs) so as to avoid ZP-specific oophoritogenic T cell epitopes (TCEs) in the ZP3-based immunogens. In this study, based on known results of mapping marmoset and bonnet monkey ZP3 (mstZP3 and bmZP3), two predictable epitopes 23–30   and   301–320 on hZP3 were first confirmed and five minimal motifs within four epitopes on hZP3 were defined using serum to recombinant hZP3a 22–176 or hZP3b 177–348 as well as a biosynthetic peptide strategy. These defined minimal motifs were QPLWLL 23–28 for hZP3 23–30, MQVTDD 103–108 for hZP3 93–110, EENW 178–181 for hZP3 172–190, as well as SNSWF 306–310 and EGP 313–315 for hZP3 301–320, respectively. Furthermore, the antigenicity of two peptides for hZP3 172–187 and hZP3 301–315 and specificity of the antibody response to these peptides were also evaluated, which produced high-titer antibodies in immunized animals that were capable of reacting to ZP on human oocytes, r-hZP3b 177–348 protein, as well as r-hZP3 172–190, r-hZP3 303–310, and r-hZP3 313–320 epitope peptides fused with truncated GST188 protein.